Sintesis Grafena Oksida Tereduksi Menggunakan Reduktor Jus Jeruk Nipis (Citrus aurantifolia) dan Aplikasinya Sebagai Adsorben Malachite Green - Said Ali Akbar; Hasby Hasby (Postgraduate, University of Mataram, 2023)
The cytotoxicity of fishes resulting from the presence of various industrial dyes in industrial effluents is a significant global concern. This study aims to synthesize Reduced Graphene Oxide (RGO) using a natural reducing agent from lime juice. The synthesis process uses a modified Hummer method. The Langmuir and Freundlich Isothermal equations are used to study the adsorption character of MG using RGO. The adsorption kinetics was studied using first and second order equations. The adsorption capacity was measured with concentration 2, 10, 50, and 100 mg L-1 of MG respectively. The results obtained are for the adsorption isotherms following Langmuir and Freundlich. Î”GÂ° shows a negative value which means the adsorption process is spontaneous. The adsorption kinetics follows the first order equation. The adsorption capacity obtained was Qm = 223.21 mg gâˆ’1 and a contact time of 20 minutes which made it a strong adsorbent for removing MG from water samples. The removal efficiency of MG by prepared adsorbents from real environmental water sample on the Ulee Lheue beach, Alue Naga beach, and the Krueng Aceh river has been implemented. The results obtained confirmed good work in the applicability of adsorbents for environmental